DESENTRALISASI ASIMETRIK DARI PENGATURAN KEPEGAWAIAN: Desentralisasi Asimetris Dalam Pengaturan Kepegawaian Terkait Efisiensi Dan Efektivitas Kinerja Birokrasi Pemerintah Pusat Dan Daerah dan 2. Perbedaan Dalam Kebijakan Rekruitmen Dan Seleksi Pegawai Antara Pemerintah Pusat Dan Daerah Terhadap Kompetensi Dan Profesionalisme Sumber Daya Manusia. - mela sari (CV Rewang Rencang, 2024)
This research aims to understand personnel arrangements related to the efficiency and effectiveness of civil servant performance in the bureaucracy as well as employee recruitment and selection policies between central and regional governments, especially regarding the competency and professionalism of human resources in a decentralized asymmetric government system. The research method used in the research is legal research using a conceptual approach. The results of the research show that the implementation of the asymmetric decentralized system of delegation of authority is not fully in line with expectations, regional government problems include issues of bureaucratic neutrality, service quality, recruitment of prospective employees, salary systems and career development, as well as the role of the civil service commission in the recruitment process for prospective civil servants In the regions, there was a lot of evidence of subjectivity so that the civil servant selection process could not produce competent civil servants. To overcome this, it is necessary to change strategies in implementing employee recruitment accompanied by changes in mindset and organizational culture that are oriented towards improving the quality of public services. Keywords: Asymmetric Decentralization, Civil Servant Performance, Recruitment policy, Indonesian Government.